1998
DOI: 10.2214/ajr.171.1.9648774
|View full text |Cite
|
Sign up to set email alerts
|

Aortic graft infection: the value of percutaneous drainage.

Abstract: treated by primary percutaneous drainage with patients who initially underwent surgery. MATERIALS AND METHODS. A retrospective reviewof 23 consecutive patientstreated for aortic graft infection was performed. Eleven patients were initially treated with per cutaneous drainage and 12 were treated with surgery. The morbidity, mortality, and postproce dural reintervention rates and clinical outcome were analyzed for each group.RESULTS.Theseptic process resolved in nine(82%)of 11patients treated withpercutane ous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 25 publications
1
24
0
3
Order By: Relevance
“…Coselli et al [3] emphasized the importance of graft coverage and elimination of dead space with viable tissue flaps. Percutaneous drainage prior to an open surgical repair or the treatment of abdominal or thoracoabdominal aortic graft infection has been reported [4][5][6]. To the best of our knowledge, although percutaneous drainage of an abdominal aortic aneurysm sac has been previously reported, drainage of an abscess located at the aortic arch is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Coselli et al [3] emphasized the importance of graft coverage and elimination of dead space with viable tissue flaps. Percutaneous drainage prior to an open surgical repair or the treatment of abdominal or thoracoabdominal aortic graft infection has been reported [4][5][6]. To the best of our knowledge, although percutaneous drainage of an abdominal aortic aneurysm sac has been previously reported, drainage of an abscess located at the aortic arch is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the use of percutaneous drainage was shown to be a successful primary therapy, with resolution of sepsis in 82% of patients compared with only 33% in the surgical group, although fluid collection was inaccurately measured in 67% of the patients in the surgical group (6). In addition, 45% of the patients in the percutaneous drainage group required open surgery due to abdominal aortic aneurysm, ruptured abdominal aortic aneurysm, or thoracoabdominal aneurysm, with no deaths reported within 30 days and one death occurring by the one-year follow-up (6). Aggressive drainage has been used as either the sole treatment or a bridge to surgical management, with an appropriate survival rate (4, 7).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Even percutaneous drainage followed by surgery has been reported. 11 A more recent review of a mixed group of nine patients, for whom major surgery was contraindicated, demonstrated that survival could be obtained by conservative management, although this group did have adjunctive procedures such as partial graft excision in three patients and percutaneous drains with three times daily instillation of antibiotics. 12 Seven of the nine patients survived, with only one case of amputation and no recurrent infection over a mean of 7.6 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%